2004
DOI: 10.1074/jbc.m406639200
|View full text |Cite
|
Sign up to set email alerts
|

The Propeptide Domain of Lysyl Oxidase Induces Phenotypic Reversion of Ras-transformed Cells

Abstract: Lysyl oxidase is an extracellular enzyme critical for the normal biosynthesis of collagens and elastin. In addition, lysyl oxidase reverts ras-mediated transformation, and lysyl oxidase expression is down-regulated in human cancers. Since suramin inhibits growth factor signaling pathways and induces lysyl oxidase in ras-transformed NIH3T3 cells (RS485 cells), we sought to investigate the effects of suramin on the phenotype of transformed cells and the role of lysyl oxidase in mediating these effects. Suramin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
119
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 53 publications
(60 reference statements)
6
119
0
Order By: Relevance
“…LOX is also a tumor suppressor and it inhibits ras-dependent transformation of fibroblasts [4,8,14]. The tumor suppressor activity of LOX has been mapped to the pro-peptide region [24] and LOX-PP inhibits tumor formation by breast cancer cells in mice [19]. In normal osteoblasts, LOX-PP accumulates in cultures [9] and recombinant LOX-PP is taken up by cells and accumulates over time associated with microtubules [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LOX is also a tumor suppressor and it inhibits ras-dependent transformation of fibroblasts [4,8,14]. The tumor suppressor activity of LOX has been mapped to the pro-peptide region [24] and LOX-PP inhibits tumor formation by breast cancer cells in mice [19]. In normal osteoblasts, LOX-PP accumulates in cultures [9] and recombinant LOX-PP is taken up by cells and accumulates over time associated with microtubules [7].…”
Section: Discussionmentioning
confidence: 99%
“…Primary vascular SMCs were grown with LOX-PP (10 μg/ml) or vehicle was then the number of viable cells per culture determined after 48 hours. The concentration of LOX-PP was based on preliminary dose response-and published studies [19,24,28]. Figure 1A shows that LOX-PP significantly inhibits the growth of SMC cultures.…”
Section: Lox-pp Inhibits Smc Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Ha-Ras-mediated transformation of NIH 3T3 fibroblasts and rat liver epithelial cells resulted in IKK complex activation through multiple pathways involving mitogen-activated protein kinases as well as PI(3)K/Akt (7,41). Furthermore, in breast cancer cells, the PI(3)K/Akt axis played a role during NF-nB activation in response to EGFR or HER-2/ neu signaling (31, 42), which could be impeded by the PTEN tumor suppressor (31) or by the pro-peptide domain of lysil oxidase (43,44). Consistent with a role of the PI(3)K/Akt axis in IKK activation, we report that TGF-a/c-Myc -derived hepatocellular carcinomas display constitutive phosphorylation Another important finding of our study is the antagonistic effect of NF-nB on c-Myc-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…LOXL-1, similarly to LOX, plays a critical role in the formation and repair of the ECM by oxidizing lysine residues in elastin and collagen, thereby stabilizing the fibrous proteins (18,27). In addition to its fibrogenic function, LOX expression is associated with tumor suppression and tumor progression, and its role in tumorigenesis appears to be dependent on cellular location, cell type and transformation status (27)(28)(29)(30)(31)(32). Microarray studies have shown that the expression of LOX is elevated in hypoxic human tumor cells (33), suggesting that the LOX expression is regulated by hypoxiainducible factor (HIF) and is associated with hypoxia in human breast, head and neck tumors (28).…”
Section: Discussionmentioning
confidence: 99%